Implementation of Audio-Visual-Based History Learning Media In the Independent Curriculum in Class XI of SMA Negeri 5 Samarinda - berliani sofyana; Muhammad Azmi (Yupa: Historical Studies Journal, 2025)
This research the aims to analyze the implementation of audio-visual media based history learning in the independence curriculum in class XI of SMA Negeri 5 Samarinda. This research uses a case study method through observation, interviews, and documentation as data collection techniques. The results of this research indicate that the implementation of audio-visual media in class XI of SMA Negeri 5 Samarinda develops understanding of complex material and learning motivation. Implementation obstacles encountered with audio-visual media include a lack of clarity in material delivery due to its too fast, unclear discussion and relevant material, limitations in technology functionality, and lack of sosial intercation between students and teachers. The perceptions of class XI SMA Negeri 5 Samarinda students show that this audio-visual media causes the level of interest of students to vary, with most being very interested while some others are less enthusiastic.